Autoestima y Aprendizaje en los estudiantes de la Universidad Nacional de Chimborazo. Riobamba. Marzo-Julio 2017. - Guaño Flores, Vanessa Estefania (2017)
The present research project permitted to relate the self-esteem levels and the learning styles in students from the National University of Chimborazo who are majoring in Educational Psychology. Self-esteem and learning are factors that contribute positively in the formation of the human being by promoting self-assessment, self-confidence and acceptance which is essential for psychological well-being, creating new thoughts to have a balanced emotional stability. Methodologically, it was a non-experimental design research due to the variables were not manipulated; the type of research was transversal with a correlational level of investigation. The population was composed by the students from the National University of Chimborazo. The sample was intentionally non-probabilistic, with 24 students from the second semester of the Educational Psychology, room “B” that takes place in the morning. The techniques used were: to measure the self-esteem level: the Coppersmith’s scale and the Honey_ Alonso survey that identified the learning styles. After performing the analysis and interpretation of results, the self-esteem levels were determined and established that the high level and the four learning styles are similar.